Acoustic properties of crystallized fat: Relation between polymorphic form, microstructure, fracturing behavior, and sound intensity. Issue 9 (19th January 2016) - Gregersen, Sandra Beyer; Povey, Malcolm J. W.; Andersen, Morten Daugaard; Hammershøj, Marianne; Rappolt, Michael; Sadeghpour, Amin; Wiking, Lars
Abstract : This study demonstrates a link between the fat crystal network, fracturing behavior, and sound emission upon breakage. SOS, PSO, PPO, and POP rich fats were characterized by SAXS/WAXS and confocal laser scanning microscopy. Simultaneous texture and acoustic analysis was conducted by the use of a texture analyzer connected with an acoustic envelope detector and augmented by a broad band microphone combined with a digital sampling oscilloscope. Results shows a high correlation between negative values of the 2nd derivative of force curves, providing a measure of the energy release, and the sound intensity ( r = 0.89, p < 0.05). No relation between acoustic properties and polymorphic behavior, crystal size, or crystal morphology was found. All fats crystallized into a β′ form within 1 day of storage. Subsequently, only the PPO and POP rich fats transformed into the β form (2–4 wk). Evaluation of the relative strength of intra‐ and interparticle links within the fat crystal network, indicate an important role of inter‐particle links for the sound intensity, whereas intra‐particle links were of less importance. It is hypothesized that strong interparticle links provide a strong rigid structure resulting in build‐up of energy during compression and a fast energy release upon breakage accompanied by sound emission. Practical applications: Results from this study provide important knowledge on acoustic properties of fat which can contribute to ensuring a suitable snap, in terms of a high intense sound upon breakage, of chocolate and confectionery products. Acoustic properties of fats are important for the snap of chocolate and confectionery products. This study demonstrates how the breakage sound intensity is significantly correlated with the negative part of the second derivate of force curves, which can be related to a rigid structure due to strong intraparticle links. Abstract : Acoustic properties of fats are important for the snap of chocolate and confectionery products. This study demonstrates how the breakage sound intensity is significantly correlated with the negative part of the second derivate of force curves, which can be related to a rigid structure due to strong intraparticle links.